PENGARUH INOVASI, RELATIVE ATTRACTIVENESS, TRUST, DAN RELATIONSHIP QUALITY TERHADAP REPURCHASE INTENTION: Study Pada Pelanggan Pasar Ikan Asap Kedungboto, Pasuruan - Rumefi, Ufi; Trisnawati , Shelyn Irmanda; Anis , Nusron; Ummah, Niswatul; Bayhaki, Muhammad (STIE PGRI Dewantara Jombang, 2023)
People's interest in culinary tourism influences their preferences. Travelers not only think about good places to visit, but they also think about what food can be enjoyed with uniqueness and comfort. The purpose of the study is to determine and explain the effect of Innovation, Relative Attractiveness, Trust and Relationship Quality on Repurchase Intention. This study uses a quantitative approach. The population in this study were smoked fish customers and a sample of 120 respondents. The test tool used multiple linear regression, T Test and Test The results of the study showed that together, Innovation, Relative Attractiveness, Trust and Relationship Quality have a significant effect on the Repurchase Intention variable, while partially Innovation, Relative Attractiveness, and Relationship Quality have a significant effect on Repurchase Intention with Relative Attractiveness being a variable that has a more dominant effect on Repurchase Intention. This is because the appeal of Kedungboto Smoked Fish Market products with low prices and good quality attracts customers to buy Kedungboto Smoked Fish Market products.